1979
DOI: 10.1037/0022-006x.47.3.500
|View full text |Cite
|
Sign up to set email alerts
|

Controlled comparison of progressive relaxation, stimulus control, and paradoxical intention therapies for insomnia.

Abstract: The effectiveness of treatment programs based on progressive relaxtion, stimulus control, and paradoxical intention was assessed in the context of sleep difficulties. The results indicated that each of the therapeutic procedures significantly reduced sleep complaints in contrast to placebo and waiting list control groups. No differences were observed among the three active techniques.The prescription of sedative hypnotics is the most frequently used treatment for primary or nonphysiologically based insomnia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(56 citation statements)
references
References 15 publications
0
55
0
1
Order By: Relevance
“…Relaxation therapies have been proven to be effective against patient-specific insomnia symptoms in a number of studies 36) . In particular, music therapy has been reported to reduce anxiety and improve quality of sleep in several studies 37,38) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relaxation therapies have been proven to be effective against patient-specific insomnia symptoms in a number of studies 36) . In particular, music therapy has been reported to reduce anxiety and improve quality of sleep in several studies 37,38) .…”
Section: Discussionmentioning
confidence: 99%
“…The education session in the present study also covered sleep stimulus control therapy procedures, such as going to bed only when sleepy. Several studies have shown that sleep stimulus control therapy is more effective than relaxation therapies in reducing the symptoms of insomnia 36) . Sleep stimulus control therapy has been shown to effectively reduce sleep-onset latency 39) and to effectively help maintain sleep 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Post-study consultations with participants showed that many had adopted relaxation training into their everyday lives. Relaxation training can be conducted at any time, regardless of location [29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…The current study suggests combining sleep hygiene education with a behavioral therapy approach such as relaxation training, stimulus control, sleep restriction, or cognitive therapy 24,26,28,29) . Relaxation training can be used at any time as a self-help approach and is considered to improve sleep quality 29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…This service subsequently motivated the subjects to listen to music and engage in aromatherapy in their private lives, which we believe contributed to the effects of the study. Previous studies have reported that stimulus control and sleep restriction are more effective in treating insomnia than relaxation training 28,29,[32][33][34] . However, the individual guidance of 30 min in the present study can be insufficient to understand and adopt stimulus control and sleep restriction into their everyday lives.…”
Section: Discussionmentioning
confidence: 99%